(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article investigates how Dokiya Humenna has managed to describe the parameters of those phenomena (feelings, ideas, experiences, abilities...) that can not be measured by concrete measures, because humanity has not invented the units of measurements for them yet. It has not developed standards and samples, but they (those phenomena) exist and influence people’s lives. Sometimes they decide their fate, decorate or discolor the world, and therefor humanity must pay attention to them and recon with their presence in this world and their dimensions, even if peculiar ones, that are based on the feeling and experiences, that is, symbol icones.